Investigation on the factors influencing construction time and cost overrun for high-rise building projects in Penang - Nor Haslinda, A.; T., Wei Xian; K., Norfarahayu; Rahmat, Muhamad Hanafi; Hasmori, Muhammad Fikri (2018)
Time and cost overruns have become one prominent issue for most construction projects around the world. Project costing and timeframe extension had been causing a lot of wastage and loss of opportunity for many parties involved. Therefore, this research was carried out to investigate the factors influencing time and cost overruns for high-rise construction projects in Penang, Malaysia. A set of questionnaires survey was distributed to the project managers who had been or currently involved in the high-rise building projects in Penang to get their input and perceptions for each factor identified as well as its frequency of occurrence. In order to rank all the factors gathered, the mean index of the most distinguishing factors and its frequency of occurrence were multiplied to get the severity index. The results revealed that for time overrun, the most predominant causes were due to design changes, inadequate planning and scheduling and poor labor productivity. Meanwhile, the predominant causes of cost overrun were poor pre-construction budget and material cost planning, inaccurate quantity take-off and materials cost increased by inflation. The significance of establishing the issues related to time and cost overruns for the high-rise building construction project is to provide a greater insight and understanding on the causes of delays, particularly among the main project players: contractors, client, and consultants.